(untitled) (Canadian Medical Education Journal, 2023)
Implication Statement The field of oncology presents a number of emotionally challenging situations for a trainee to navigate which might not have been previously encountered in training. With the assistance of a guide, reflecting on such situations can be helpful; however, no tool exists in the literature specifically for clinical oncology situations and tailored to provide trainees guidance through the reflective process. Consequently, we present a self-guided reflection tool design using four established reflection models and improved over three iterations of feedback.